Implementation of Best Practice Recommendations for Palliative Care in German Comprehensive Cancer Centers - Gahr, Susanne; Lödel, Sarah; Berenot, Julia; Thomas, Michael; Ostgathe, Christoph (Oncologist, 2019)
Background From 2014 to 2017, the Palliative Medicine Working Group developed and published best practice recommendations for the integration of palliative care in Comprehensive Cancer Centers (CCCs) in Germany. To evaluate the implementation level of these recommendations in the CCCs an online survey was performed. Based on the results of this study, strategic tandem partnerships between CCCs should be built in order to foster further local development. Materials and Methods Directors of all CCCs were contacted by e-mail between December 2017 and February 2018. At the time of the survey, 15 CCCs were funded by the German Cancer Aid. The level of implementation of the recommendations in individual CCCs was established using a transtheoretical model. Results Between December 2017 and February 2018, all 15 contacted directors or their representatives of the CCCs took part in the survey. More than two thirds of the CCCs have a palliative service as well as a day clinic and palliative outpatient clinic. Regional networking and the provision of a palliative care unit were approved by all CCCs. Conclusion The publication of best practice recommendations was a milestone for the integration of palliative care in the CCCs. The majority of the German CCCs already fulfill essential organizational and structural requirements. There is a particular need for optimization in the provision of a basic qualification for general palliative care and emergency admission personnel. Implications for Practice In 2017, the Palliative Medicine Working Group in the network of the German Comprehensive Cancer Centers (CCCs) published the best practice recommendations it had developed for the integration of palliative medicine in CCCs in Germany. In order to evaluate the level of implementation of the recommendations, an online survey of the CCC directors was established. The majority of German CCCs fulfil elementary organizational and structural requirements. However, there is still room for improvement in the provision of a basic qualification for general palliative care and emergency admission personnel.
CRIS-Team WoS Importer:2019-09-27